Pemberdayaan UMKM Bawang Goreng melalui Modernisasi Produksi, Penguatan Branding, dan Ekspansi Pemasaran Digital - Bagus Cahyo Shah Adhi Pradana; Hikmah Husniyah Farhanindya; I Dewa Ketut Raka Ardiana; Nadia Aulia Ferlinda; Adiska Putria Nova; Bryan Lie (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic development, particularly in the food processing sector. However, many still face challenges in production efficiency, product branding, and digital marketing. This community service program aims to empower a fried shallot SME through production modernization, branding enhancement, and digital marketing expansion. The methods implemented include training on operating appropriate technology tools such as spinner fryers and oil drainers, mentoring in packaging and logo design, and digital marketing workshops using Instagram and online marketplaces. The results show a 40% increase in production efficiency, improved product quality, and higher engagement in online sales channels. This activity demonstrates that combining technological innovation with strategic branding and digital marketing significantly increases the competitiveness and sustainability of local SMEs.